Gaudichaudione H Inhibits Inflammatory Responses in Macrophages and Dextran Sodium Sulfate-Induced Colitis in Mice - Jiang, Yiwen; Xiao, Lianbo; Fu, Wenwei; Tang, Yuexun; Lertnimitphun, Peeraphong; Kim, Nami; Zheng, Changwu; Tan, Hongsheng; Lu, Yue; Xu, Hongxi (Frontiers in Pharmacology, 2020)
Macrophages-involved inflammation is considered to induce the damage in various diseases. Herein, novel therapeutics inhibiting over-activation of macrophages could prove an effective strategy to prevent inflammation-related diseases. Gaudichaudione H (GH), which is a natural small molecular compound isolated from Garcinia oligantha Merr. (Clusiaceae) has previously been demonstrated its anti-cancer effects on several cancer cell lines. However, no report has been published about the anti-inflammatory effect of GH to date. This study aims to examine the anti-inflammatory effects and potential molecular mechanism of GH, and provide new insights towards the treatment of inflammation. GH inhibited nitric oxide (NO) production, inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) expression, cytokine interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) production and mRNA expression to attenuate inflammatory responses in lipopolysaccharide (LPS)-induced RAW 264.7 cells or stimulated bone marrow-derived macrophages (BMDMs). GH inhibited nuclear factor-κB (NF-κB) and mitogen-activated protein kinase (MAPK) pathways, the nuclear translocation of transcription factors NF-κB and AP-1, as well as upstream signaling of the toll-like receptor 4 (TLR4)-myeloid differentiation primary response 88 (MyD88) pathway in stimulated macrophages. Furthermore, the result of the intracellular signaling array showed that the phosphorylation of adenosine 5’-monophosphate-activated protein kinase-α (AMPKα), proline-rich akt substrate of 40 kDa (PRAS40) and p38 could be down regulated by GH in BMDMs, indicating that the mechanism by which GH inhibited inflammation may be also associated with the energy metabolism pathway, PRAS40-mediated NF-κB pathway, cell proliferation, apoptosis and autophagy, etc. In addition, GH alleviated dextran sodium sulfate (DSS)-induced colitis in mice by ameliorating weight loss, stool consistency change, blood in the stool and colon shortening. GH decreased the protein and mRNA levels of IL-6 and TNF-α, iNOS and COX-2 mRNA expression, the activation of NF-κB and MAPK pathways, the phosphorylation of AMPKα and PRAS40, histological damage and infiltration of macrophages in the colons of mice with DSS-induced colitis. Taken together, our results support that GH exerts the anti-inflammatory effects in macrophages in vitro through regulation of NF-κB and MAPK pathways, and DSS-induced colitis mouse model in vivo. These findings suggest that GH may be a promising candidate in treating macrophage-related inflammatory disease.